License Revocation of Insurance Companies and Legal Protections of the Policyholders - Ayup Suran Ningsih (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: Revocation of insurance company business licenses certainly has an effect on the insured as consumers who must be protected. In this case, OJK oversees the flow of revocation of business licenses, which requires insurance companies to report settlement of corporate obligations.Purpose/Objective Study: This research discussed the types of license revocation of the insurance companies and legal protections of the policyholders when this revocation happened.Design/Methodology/Approach: This study is a qualitative one, which uses a normative juridical method. It approached by the juridical research that uses primary data in the form of Acts or Regulations.Findings: The types of business license revocation of insurance companies are divided into 4, namely: (1) cancellation of business licenses due to administrative sanctions that are gradually applied; (2) revocation of business licenses due to company requests; (3) dismissal of business licenses due to bankruptcy, and; (4) revocation of business licenses due to the merging or business combination. The respective procedures are governed by the relevant OJK Regulations. The repeal of insurance company business licenses certainly has an effect on the insured as consumers who must be protected. In this case, OJK oversees the flow of revocation of business licenses, which requires insurance companies to report settlement of corporate obligations.